APPLICATION OF SWOT ANALYSIS FOR FORMULATING PRODUCTION QUALITY IMPROVEMENT STRATEGY AT PT DELTA JAYA MAS - Nando Janitra Prasojo; Refiana Dwi Maghfiroh (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
This research is motivated by the urgency of addressing the high product defect rate at PT Delta Jaya Mas, which is weakening its competitiveness in the global hose industry. The primary objective of this study is to formulate a comprehensive strategy for improving production quality by mapping the company's internal and external factors. Using qualitative descriptive methods, data were obtained from participant observation, in-depth interviews, and documentation, which were then analyzed using the IFAS, EFAS, and TOWS matrices. The analysis revealed that despite the company's strong business reputation and raw material certification, operational performance was still hampered by a reactive machine maintenance system and supply fluctuations. As a solution, this study recommends an aggressive strategy focused on export market expansion and product customization. Operationally, the company is encouraged to transform its maintenance system into a preventive one, as well as diversify its suppliers and train its workforce across functions. These strategic steps are crucial for minimizing product damage, addressing price pressures from imported products, and ensuring the long-term sustainability of production quality. ABSTRAK Penelitian ini dilatarbelakangi oleh urgensi penanganan tingginya tingkat cacat produk di PT Delta Jaya Mas yang melemahkan daya saing di tengah kompetisi industri selang global. Tujuan utama studi ini adalah merumuskan strategi komprehensif untuk peningkatan kualitas produksi dengan memetakan faktor internal dan eksternal perusahaan. Melalui metode deskriptif kualitatif, data diperoleh dari observasi partisipatif, wawancara mendalam, dan dokumentasi, yang kemudian dianalisis menggunakan matriks IFAS, EFAS, serta TOWS. Hasil analisis mengungkapkan bahwa meskipun perusahaan memiliki fondasi kuat dalam reputasi bisnis dan sertifikasi bahan baku, kinerja operasional masih terhambat oleh penerapan sistem pemeliharaan mesin yang bersifat reaktif dan fluktuasi pasokan. Sebagai solusi, penelitian ini merekomendasikan strategi agresif yang berfokus pada ekspansi pasar ekspor dan kustomisasi produk. Secara operasional, perusahaan didorong untuk mentransformasi sistem pemeliharaan menjadi preventif, serta melakukan diversifikasi pemasok dan pelatihan tenaga kerja lintas fungsi. Langkah-langkah strategis ini krusial untuk meminimalkan kerusakan produk, menghadapi tekanan harga dari produk impor, serta menjamin keberlanjutan kualitas produksi jangka panjang.